Illinois Waterfowl Surveys and Investigations W-43-R-65-B Annual Progress Report FY2018 - Askren, Ryan J.; Malanchuk, Luke J.; Lancaster, Joseph D.; Yetter, Aaron P.; Hine, Chris S.; Hagy, Heath M.; Ward, Michael P. (Illinois Natural History Survey, 2018)
We monitored cellular-collared Canada geese in the Greater Chicago Metropolitan Area, specifically their use of space near Midway International Airport(MWD).Extensions of runways 13 and 31 were intersected more frequently (13.26% of transitional movements, x = 225) than extensions of runways 4 and 22 (2.52% of transitional movements, x = 76). We recorded 18 instances of movements intersecting airspace over runways at MDW (0.60% of transitional movements).The majority of transmittered Canada geese bred within the range of the temperate-nesting, Mississippi Flyway Giant Population with the exception of one male that appeared to be part of the subarctic-nesting, Mississippi Valley Population based on timing of migration and movement pattern indicating nesting. On average, 24.6% of transmittered geese underwent molt migrations during 2015–2017.We monitored the chronology and distribution of shorebirds aerially in the IRV during autumn and spring migration. Total number of shorebirds peaked in the IRV during autumn 2017 at 18,120, and averaged 12,024 birds/flight. We noted a positive trend with shorebird abundance and mudflat availability as river levels decreased in the IRV during August 2017. We documented lower shorebird numbers during spring 2018 in the IRV with a peak of 3,320 birds and an average of 2,527 birds/flight.Fluctuating water levels during migration drastically reduced the availability of shorebird habitat in the IRV during spring.Aerial detection of shorebird flocks was 97% and aerial count bias was 89.1% (range 0–250%) for total shorebirds. Count bias averaged 101.1% for large shorebirds and 80.4% for small shorebirds. not peer reviewed Open Restriction set for Item 107946 on 2018-10-03T21:40:57Z with date null by braxton@illinois.edu. Submitted by Susan Braxton (braxton@illinois.edu) on 2018-10-03T21:47:41Z No. of bitstreams: 1 INHS2018_28.pdf: 1879736 bytes, checksum: fac31a67a30dceb150ed16ef18bfc6a0 (MD5) Made available in DSpace on 2018-10-03T21:47:41Z (GMT). No. of bitstreams: 1 ...